Ocena wewnętrznych uwarunkowań konkurencyjności grup producenckich województwa małopolskiego z wykorzystaniem modelu regresji logistycznej - Domagalska-Grędys, Marta (Estimation of Internal Conditioning of Producer Groups Competitiveness in the Małopolska Region Using the Logistic Regression Model, 2006)
The analysis presented in the article aims at the studies on internal factors determining the efficiency of team work (the value of success, the strength of desire for group success, group cohesion). The research supposed to resolve the problem is which variables influence a change in group members' incomes.The analysis of logistic regression is used to demonstrate the probability of individual variables effect on a change of farm incomes after its accession into a producer group. In the tested sample of 400 producers from the Małopolska province the accession into the group positively influenced the incomes, i.e. increased them and lowered the costs of the members for c.a. 22 per cent. The logistic regression analysis demonstrates that group cohesion has the greatest influence on higher incomes since its raise by 1 per cent increased the chance of larger incomes by 21 per cent. The results indicate the direction of trainings aimed at improving group cohesion, which may also improve the effectiveness of farmer group activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 180-186